Green gentrification or gentrified greening: Metropolitan Melbourne. (September 2021) - Sharifi, Farahnaz; Nygaard, Andi; Stone, Wendy M.; Levin, Iris
Abstract: Urban greening is a tool of urban planning to mediate problems related to urban living and betterment of residents' quality of life. Given the inequitable distribution of this urban public health infrastructure, increasing green area within disadvantaged neighborhoods is one of the contemporary initiatives in urban planning. However, some argue that urban greening can have mixed consequences. Specifically, urban greening efforts may lead to "green gentrification", and as a result, can unintentionally displace lower income residents and increase inequities. Despite this, few studies have investigated the relationship between gentrification and urban greening. We aim to empirically answer the questions, "Does urban greening lead to gentrification?" or "Does gentrification lead to urban greening?". We draw on green space data from Landsat and census socioeconomic data over 1996–2016 to analyze the historical data of urban greenness changes and area profile transitions. The result does not indicate any statistically significant evidence that urban greening catalyzes gentrification, but does show that gentrification actuates urban greening. The policy implications are discussed. Highlights: Urban greening is not a catalyzer of gentrification. Growth in suburbs' relative income actuates urban greening. This study adds a new concept and understanding of "gentrified greening". An innovative method to analyze the causality direction of gentrification and urban greening is presented. Monitoring urban greening and its potential effects need to be paramount.